(untitled) (Scientific journal of the Fergana State University, 2024)
This article is devoted to the foreign policy of the Republic of Uzbekistan to strengthen regional and international cooperation in order to ensure peace, stability and sustainable development in the Central Asian region. The article uses chronological and systematic periodic data, comparative and quantitative methods. More than ten scientific works on this topic are used to explain “Strengthening regional and international cooperation to ensure security and stability in the Central Asian region”. In addition, the researchers used various materials to collect data related to the study.